THE INNOVATIVE STRATEGIES FOR LEARNING INDONESIAN LANGUAGE AND LITERATURE IN HIGHER COLLEGE TO IMPROVE LITERACY - Yollanda Octavitri (Jurnal Scientia, 2023)
This research aims to explore and analyze innovative strategies in learning Indonesian Language and Literature in a higher education environment as an effort to increase student literacy. A qualitative approach was used to explore students' experiences, perceptions and learning outcomes as well as lecturers' opinions regarding the innovative strategies implemented. This research method involves case studies at several universities, with data collection through in-depth interviews with lecturers and students, class observations, and analysis of curriculum documents. Data analysis was carried out thematically to identify patterns and main findings regarding the effectiveness of innovative strategies in increasing literacy. It is hoped that the results of this research can contribute to the development of learning models that are relevant to students' current literacy needs. It is hoped that the practical implications of these findings will provide guidance for universities in designing and implementing innovative strategies in learning Indonesian Language and Literature to increase student literacy levels.